A Review of Feminist Legal Theory on Abortion Regulations for Rape Victims in Indonesia - Asyrof, Muhammad Fiqri; Lukmanula, Fikri Rizki; Arya, Mohammad; Asmara, Teddy; Noupel, Muhammad (Jurnal Legisci, 2024)
The purpose of this study is to review and evaluate abortion regulations for rape victims, especially the requirements outlined in the Health Law and Government Regulation No. 61 of 2014 concerning Reproductive Health, using feminist legal theory as an analysis framework. This study uses an extra-doctrinal methodology outside the laws and regulations, emphasizing feminist legal theory as the basis of thought. The findings suggest that abortion regulations for rape victims still largely ignore women's life experiences and put them in difficult situations. The marginalization of women victims of rape in accessing safe abortion is a consequence of the gestational age limit for abortion, which fails to acknowledge the different experiences of women and treat them as a homogeneous group. To effectively address this issue, it is critical to involve the participation of women who have experienced rape, including victims of sexual violence, in the development of policies related to abortion for rape victims.